2007
DOI: 10.31421/ijhs/13/3/743
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of old Hungarian apple varieties

Abstract: Altogether 40, mainly old Hungarian apple varieties were screened with six previously described microsatellite markers. A total of 71 polymorphic alleles were detected (average 11.8 alleles/locus) and the heterozygosity of markers averaged very high (0.8). The genetic variability among the genotypes proved to be so remarkable that as few as three markers from the applied six were enough to distinguish between the 40 varieties. This was also confirmed by the cumulative probability of obtaining identical allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…The two variants of 'Beregi sóvári' were also found to differ. Wichmann et al (2007) investigated the cultivars 'Nyári sóvári' and 'Puha sóvári' , and although SSR values are often not directly comparable between different studies, they did not detect the same fragment lengths at the equivalent loci as have been found in the present work.…”
Section: Evaluation Using the Upov Number Codecontrasting
confidence: 55%
“…The two variants of 'Beregi sóvári' were also found to differ. Wichmann et al (2007) investigated the cultivars 'Nyári sóvári' and 'Puha sóvári' , and although SSR values are often not directly comparable between different studies, they did not detect the same fragment lengths at the equivalent loci as have been found in the present work.…”
Section: Evaluation Using the Upov Number Codecontrasting
confidence: 55%
“…In cluster analysis (Figure 4), all triploids but ORCA were classified separately from the diploid accessions, as reported other authors (Pereira-Lorenzo et al 2007;Garkava-Gustavsson et al 2008;Wichmann et al 2018). This separation can also be explained by the fact that five of the triploids accessions belong to 'Reineta' cultivar or are presumably related to this genotype.…”
Section: Pcoa Bayesian Analysis Of Populations and Cluster Analysessupporting
confidence: 78%
“…In the apple collection studied byGalli et al (2005) 4 SSR were needed to discriminate 66 commercial cultivars. In the study ofWichmann et al (2018) only three loci discriminated 40 accessions. Larger collections may require more loci, as seven loci were needed to discriminate the 1,127 accessions fromPoles et al (2018) study.…”
mentioning
confidence: 95%
“…Heirloom apple varieties possess a robust genetic background that grants them high tolerance to major modern-day apple diseases. They have adapted to various climates and soils over time, showcasing their resilience against diseases, making them valuable for apple breeding (Wichmann et al, 2007). Notably, Papp et al (2016) found resistance against apple scab and powdery mildew in heirloom cultivars in Hungary, which likely comes from multiple genes.…”
Section: Vitality Against Major Pestsmentioning
confidence: 99%
“…Furthermore, regional heirloom cultivars boast a genetic background conducive to breeding for organic and low-input systems. Breeding for such systems, emphasizing vitality and reduced vulnerability to major diseases (Ristel et al, 2016), recognizes certain heirloom varieties exhibiting high disease tolerance and simultaneously producing quality apples (Wichmann et al, 2007). Heirloom cultivars can be further improved and bred for productivity and unique traits under organic conditions, making them ideal for such farming systems.…”
Section: Climate Hardiness and Suitability For Organic Farming Systemsmentioning
confidence: 99%